Analysis of Factors Affecting Prices Indonesian Gold Spot With ARDL Model - sasrinawati, sasrinawati; Husein, Ratna; Nailufar, Fanny; Ichsan, Ichsan (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study examines the impact of macroeconomic variables—namely inflation and exchange rates—on Indonesian gold spot prices from 1995 to 2018, employing the Autoregressive Distributed Lag (ARDL) model. The study seeks to comprehend the short-term and long-term correlations among these variables. Time series data were obtained from the Indonesian Central Statistics Agency, Index Mundi, and the Gold Price Chart. The findings indicate that, in the near term, inflation negatively and significantly affects gold prices, however, in the long term, it positively and significantly influences them. Likewise, the exchange rate exerts a substantial and adverse impact in both the short and long run, suggesting that a stronger Rupiah generally elevates gold prices. The ARDL model validates the existence of a cointegrated relationship among the variables, corroborated by the limits testing methodology. Diagnostic assessments confirm the stability and reliability of the calculated model. These findings indicate that the regulation of inflation and exchange rates is essential for maintaining gold price stability in Indonesia.